Phase I dose-escalation study of afatinib, an ErbB family blocker, plus docetaxel in patients with advanced cancer. (February 2013) - Marshall, John; Shapiro, Geoffrey I; Uttenreuther-Fischer, Martina; Ould-Kaci, Mahmoud; Stopfer, Peter; Gordon, Michael S
Aims: To determine the maximum tolerated dose (MTD), safety and anti-tumor activity of afatinib combined with docetaxel in advanced cancer.Patients & methods: The MTD was determined from dose-limiting toxicities in the first cycle.Results: Thirty-one patients received 10, 20 and 30 mg oral afatinib, plus 60 and 75 mg/m 2 intravenous docetaxel (six cohorts; 3-week cycles). The MTD of afatinib was 20 mg/day (days 2–21) with 75 mg/m 2 docetaxel (day 1). Dose-limiting toxicities were grade 3/4 diarrhea (n = 3) and febrile neutropenia (n = 6). Most frequently occurring adverse events were diarrhea, neutropenia and rash. Disease stabilization occurred in 14 patients.Conclusion: Afatinib 20 mg/day plus docetaxel was suboptimal and the study could not yield Phase II dose recommendations. The combination resulted in a manageable safety profile.